Hydrobiological research of fish ponds on the southern catchment area of Lake Balaton - Körmendi, Sándor (Acta Scientiarum Socialium, 2013)
Hydrobiological research of fish ponds on the southern catchment area of Lake Balaton This article is designed to bind former fish production in fish ponds in the south basin of Lake Balaton to the present work, and thus provide the basis for efficient, environmentally friendly technology and development. We also aim to illustrate the problems that can contribute to the solution of the protection of the waters of the southern basin of the lake and water quality.
Keywords: hydrobiology; fish ponds; water quality; zooplankton